Differential growth responses in seedlings of ten species of Dipterocarpaceae to experimental shading and defoliation - Paine, C; Stenflo, M; Philipson, C; Saner, P; Bagchi, R; Ong, R; Hector, A (2012)
The responses of plants to shade and foliar herbivory jointly affect growth rates and community assembly. We grew 600 seedlings of ten species of the economically important Dipterocarpaceae in experimental gradients of shading (0.3-47.0% of full sunlight) and defoliation (0, 25%, 50% or 75% of leaf area removed). We assessed stem diameters initially, after 2 and 4 mo, and calculated relative growth rates (RGR) with a linear model. Shading interacted with defoliation, reducing RGR by 21.6% in shaded conditions and 8.9% in well-lit conditions. We tested three hypotheses for interspecific trade-offs in growth responses to shading and defoliation. They could be positively related, because both reduce a plant's access to carbon, or inversely related because of trade-offs between herbivore resistance and tolerance. We observed, however, that species varied in their response to shading, but not defoliation, precluding an interspecific trade-off and suggesting that plants tolerate shade and herbivory with differing strategies. Shading most strongly reduced the growth of species with less-dense wood and larger seeds. The strong and variable growth responses to shade, contrasted with the weak and uniform responses to defoliation, suggest that variation in light availability more strongly affects the growth of tropical tree seedlings, and thus community assembly, than does variation in herbivory. Copyright © 2012 Cambridge University Press.